CHALLENGES OF DIGITALIZATION OF SMES (CASE STUDY IN TRADITIONAL CRAFTSMEN IN TASIKMALAYA) - Pandu Adi Cakranegara; Sujana Donandi Sinuraya; Dedi Rianto Rahadi (President University, 2021)
The Internet not only provides advancesin technology, but more than that the internet connects individuals. In Indonesia today there are several large startups that utilize the power of ecomony sharing starting from Gojek, Tokopedia, Bukalapak and many other startups. Go Jek not only brings together a vehicle owner with people who need to travel but also brings together a food vendor with people who want to order food. The same goes for Tokopedia and Open Lapak which have helped small retailers own online stores. Not to mention social media which provides an opportunity for small entrepreneurs to be able to promote their trade. The question of this research is why with all the progress and facilities available it is still difficult for SMEs to take advantage of all these facilities? This research consists of several parts. The first part of this study examines how the internet affects the fairies of life in Indonesia. The second part is that this research discusses how ideally a business utilizes internet technology. And the third part of this study talks about why there is a difference in the field between the use of the internet and the potential it should be. Keywords: Internet, SMEs, digitization, social media marketing